Development of "Religion Mazes For Kids" Educational Tools to Enhance the Religious and Moral Values of Children Aged 4-5 Years - Roudhohtin Hasanah; Umi Masturoh; Bilkisu Garba Ilah (Indonesian Journal of Early Childhood Educational Research (IJECER), 2024)
This study aims to develop an educational game tool called "Religion Mazes for Kids" to enhance the religious and moral values of children aged 4-5 years. Utilizing a research and development (R&D) method and needs analysis through surveys, this research produces a product whose feasibility is tested using descriptive quantitative analysis, including validation tests, initial field trials, and extensive field trials. The results indicate that this tool is suitable for use, with validation from material and media experts showing a "very good" category (scores of 4.75 from material experts, 4.46 from media experts, and 4.62 from classroom teachers). Improvement in children's abilities is evident from the pretest and posttest tables, with a significance value (2-tailed) of 0.002, indicating that H0 is rejected and H1 is accepted. These findings suggest that integrating educational games like "Religion Mazes for Kids" into early childhood learning can effectively foster the development of religious and moral values in young children.┬á┬á